The impact of long-term care interventions on healthcare utilisation among older persons: a scoping review of reviews - Nur Zahirah Balqis-Ali; Suhana Jawahir; Yee Mang Chan; Amanda Wei-Yin Lim; Ummi Wahidah Azlan; Sal Sabila Mohd Shaffie; Weng Hong Fun; Shaun Wen Huey Lee (BMC Geriatrics, 2024)
Abstract Background As the ageing population grows, the demand for long-term care (LTC) services will rise, concurrently amplifying healthcare utilisation. This review aims to examine and consolidate information on LTC interventions that influence healthcare utilisation among older persons. Methods A scoping review was performed through a systematic search in PubMed, EBSCO CINAHL, EBM Reviews - Cochrane Database of Systematic Reviews, Embase, APA PsycInfo, EBM Reviews - Health Technology Assessment, and EBM Reviews - NHS Economic Evaluation Database. Systematic reviews with meta-analyses published between 1 January 2010 and 2 June 2022 among older persons aged 60 and above were included. The characteristics of LTC interventions were mapped to the World Health Organization (WHO) Healthy Ageing Framework. The effect sizes of healthcare utilisations for LTC interventions were recalculated using a random-effects model. The methodological quality was assessed with the AMSTAR-2 checklist, while the quality of evidence for each association was evaluated using GRADE. Results Thirty-seven meta-analyses were included. The most prominent domain of the healthy ageing framework was managing chronic conditions. One hundred twelve associations between various LTC interventions and healthcare utilisations were identified, with 22 associations impacting healthcare utilisation. Four interventions were supported by suggestive or convincing evidence. Preventive home visits were found to reduce hospital admission (OR: 0.73, 95% CI: 0.59, 0.91, p = 0.005), caregiver integration during discharge planning (OR: 0.68, 95% CI: 0.57, 0.81, p < 0.001), and continuity of care (OR: 0.76, 95% CI: 0.61, 0.95, p = 0.018) reduced hospital readmission, and perioperative geriatric interventions reduced the length of hospital stay (MD: -1.50, 95% CI: -2.24, -0.76, p < 0.001). None of the associations impacted emergency department visits, medication use, and primary care utilisations with convincing evidence. Most reviews received low methodological quality. Conclusion The findings suggest that LTC interventions could benefit from transitioning to a community-based setting involving a multidisciplinary team, including carers. The spectrum of services should incorporate a comprehensive assessment to ensure continuous care.